Dysregulated metabolic enzymes and metabolic reprogramming in cancer cells - Sreedhar, Annapoorna (Biomed Rep, 2018)
Tumor cells carry various genetic and metabolic alterations, which directly contribute to their growth and malignancy. Links between metabolism and cancer are multifaceted. Metabolic reprogramming, such as enhanced aerobic glycolysis, mutations in the tricarboxylic acid (TCA) cycle metabolic enzymes, and dependence on lipid and glutamine metabolism are key characteristics of cancer cells. Understanding these metabolic alterations is crucial for development of novel anti-cancer therapeutic strategies. In the present review, the broad importance of metabolism in tumor biology is discussed, and the current knowledge on dysregulated metabolic enzymes involved in the vital regulatory steps of glycolysis, the TCA cycle, the pentose phosphate pathway, and lipid, amino acid, and mitochondrial metabolism pathways are reviewed.